PENINGKATAN EFISIENSI OPERASIONAL MELALUI OPTIMALISASI PROSES TRANSAKSI DAN PENGELOLAAN INVENTARIS DI PT. BANK PEMBANGUNAN DAERAH, TBK CABANG LAMONGAN - Lia Zusnita S; Lia Nirawati (Cahaya Ilmu Bangsa, 2024)
Operational efficiency is a key factor in organizational success, especially in the complex banking industry. This study evaluates the mail, transaction, and inventory administration systems at PT. Bank Pembangunan Daerah, Tbk Lamongan Branch and identifies optimization strategies that can be applied. Through literature and field studies, data on mail management, daily transaction recording, and inventory were collected. The focus of the study is the application of digital technology to improve operational efficiency, including a structured mail administration system and transaction recording using BO23K documents. The results show that the integration of technologies such as Business Intelligence & Analytics (BI&A) has a positive impact on the efficiency and accuracy of the transaction process. However, challenges such as reliance on manual processes in inventory management remain. Recommendations include increasing digitalization through barcode scanners, transaction automation with artificial intelligence (AI), and strengthening digital infrastructure and data protection to improve the efficiency and transparency of bank operations.